1999
DOI: 10.1007/s11626-999-0114-5
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative aspects of the selective killing of transformed cells by methotrexate in the presence of leucovorin

Abstract: A quantitative study was made of the cytotoxicity of methotrexate (MTX) for nontransformed and transformed NIH 3T3 cells in the presence and absence of leucovorin. The study was preceded by an analysis of the growth rates of the cells at low and high population density combined with low and high concentrations of calf serum (CS). The reduced maximal growth rates of the transformed cells at low population densities relative to the nontransformed cells reinforced earlier evidence that heritable damage involving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous studies reported that Pyr effects are mainly mediated by its antifolate activity in melanoma cells [10]. To investigate whether the antifolate activity of MBP could contribute to its antiproliferative effects in melanoma cells, we tested the apoptosis-inducing potential of MBP in the Mel501 cell line pre-treated with the reduced form of folate Leucovorin (LV, N 5 -formyltetrahydrofolate), a drug widely used to counteract the effects of antifolates [31]. In these experiments, Mel501 cell lines were treated with LV alone and in combination with Pyr (8 μg/ml) and MBP (0.8 μg/ml), after which apoptotic cell death was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported that Pyr effects are mainly mediated by its antifolate activity in melanoma cells [10]. To investigate whether the antifolate activity of MBP could contribute to its antiproliferative effects in melanoma cells, we tested the apoptosis-inducing potential of MBP in the Mel501 cell line pre-treated with the reduced form of folate Leucovorin (LV, N 5 -formyltetrahydrofolate), a drug widely used to counteract the effects of antifolates [31]. In these experiments, Mel501 cell lines were treated with LV alone and in combination with Pyr (8 μg/ml) and MBP (0.8 μg/ml), after which apoptotic cell death was evaluated.…”
Section: Resultsmentioning
confidence: 99%